Impact of Dose of Combined Conventional and Robotic Therapy on Upper Limb Motor Impairments and Costs in Subacute Stroke Patients: A Retrospective Study - Pila, Ophélie; Koeppel, Typhaine; Grosmaire, Anne-Gaëlle; Duret, Christophe (Frontiers in Neurology, 2022)
Introduction Robot-based training integrated into usual care might optimize therapy productivity and increase treatment dose. This retrospective study compared two doses of an upper limb rehabilitation program combining robot-assisted therapy and occupational therapy on motor recovery and costs after stroke. Methods Thirty-six subacute stroke patients [Fugl-Meyer Assessment (FMA) score 32 ± 12 points; mean ± SD] underwent a combined program of 29 ± 3 sessions of robot-assisted therapy and occupational therapy. Scheduled session time for the higher dose group (HG) was 90 min (two 45-min sessions; n = 14) and for the lower dose group (LG) was 60 min (two 30-min sessions; n = 22). Pre-/post-treatment change in FMA score (ΔFMA, %), actual active time (min), number of movements and number of movements per minute per robot-assisted therapy session were compared between groups. The costs of the combined programs were also analyzed. Results ΔFMA did not differ significantly between groups; the HG improved by 16 ± 13 % and the LG by 11 ± 8%. A between-group difference was found for actual active time (p = 1.06E−13) and number of movements (p = 4.42E−2) but not for number of movements per minute during robot-assisted therapy: the HG performed 1,023 ± 344 movements over 36 ± 3 min and the LG performed 796 ± 301 movements over 29 ± 1 min. Both groups performed 28 movements per minute. The combined program cost was €2017 and €1162 for HG and LG, respectively. Conclusions Similar motor improvements were observed following two doses of movement-based training. The reduction in scheduled session time did not affect the intensity of the practice and met economic constraints.